“It Feels Like a Life’s Work”: Recordkeeping as an Act of Love - Douglas, Jennifer; Alisauskas, Alexandra (Archivaria)

(untitled) (Association of Canadian Archivists, 2021)
By considering a set of in-depth interviews with eight bereaved mothers, this article seeks to explore ideas about what records are and what they do. Working to centre the voices and experiences of the bereaved mothers, the article first discusses some of the objects, events, places, and bodily traces they identified that function as records. It next considers the roles records and recordkeeping played for the parents interviewed, identifying four types of records work: proving life and love, parenting, continuing a relationship, and imagining. Records and recordkeeping are shown to be instrumental in the ongoing processing of traumatic loss as well as in the significant work of ensuring a life has meaning and is acknowledged. Finally, the interviews with parents also showed how deeply imbricated are love and grief as emotions and as motivations for recordkeeping, and the article ends by articulating a call for archivists to learn to “look with love.”